Vencer a Medusa - Soler Gallo, Miguel (Verba hispanica, 2015)
This paper presents an analysis of the traditional ideal of women in the first romance novel of Carmen de Icaza, a preeminent author in postwar Spanish literature. In the novel, two female models, an angel, representing the protagonist and the idea of traditional femininity, and the monster, who plays the antagonist and reflects the diametrically opposing view of morality to that imposed by the patriarchal society. In this novel Icaza spreads her conservative ideology to the female readers, mostly consumers of this kind of literature in the period after the Spanish Civil War, and emphasizes the values that should prevail in society.
Keywords: Icaza, Carmen de, 1899-1979; Spanish literature; španska književnost; ljubezenski roman; ženski liki; tradicionalizem